Probiotic-based cultivation of Clarias batrachus: importance and future perspective - Ganguly, Arindam; Banerjee, Amrita; Mandal, Asish; Mohapatra, Pradeep K. Das (Acta Biologica Szegediensis, 2019)
Clarias batrachus (Linn.) is widely recognized in Indian sub-continent for its nutritional and economic significance. At present, it remains at a merely vulnerable state. Pathogenic infections, diminution of natural habitats and introduction of allied exotic fishes are the causes of productivity constraint, particularly in Southern Asia. Conversely, African cat fish Clarias gariepinus has been significantly identified as a potential threat to biodiversity, despite being its large scale cultivation across the world. Thus emphasis on indigenous C. batrachus farming is becoming inevitable. Currently, screening of autochthonous probiotic organisms for the cultivation of C. batrachus in semi-intensive manner is getting importance. At the same time, molecular omics-based technologies are also gaining considerable attention to identify potential probiotic markers. This review provides an overall concept of probiotics, its application and future perspectives in relation to the cultivation of C. batrachus.